MENINJAU ILMU DIGITAL FORENSIK TERHADAP BUKTI ELEKTRONIK DALAM TINDAK PIDANA INFORMASI DAN TRANSAKSI ELEKTRONIK - Gemilang, Herdino Fajar (Universitas Kapuas, 2024)
Digital forensics is a branch of forensic science used for the investigation and examination of a case involving the analysis of material (data) and the discovery of content on digital devices. The focus of this research aims to assess the application of digital forensic science by investigators to support the identification of a case, swiftly and accurately locating evidence, and revealing the reasons and motivations behind the actions taken by the perpetrator. The Indonesian Code of Criminal Procedure (KUHAP) does not explicitly regulate the admissibility of electronic evidence, which is related to the principle of legality stating that Law No. 11 of 2008 on Information and Electronic Transactions (ITE) in Article 54, paragraph (1) allows electronic data to be used as admissible evidence. The legality of electronic evidence is also addressed in the ITE Law in Chapter III concerning Information, Documents, and Electronic Signatures, as well as the explanations in Article 44 and Article 5 of the ITE Law. Referring to the rules of evidence provided in the KUHAP, there must be a means of examination for electronic evidence to establish its admissibility in court, similar to other forms of evidence, involving both formal and substantive requirements. The research method employed in this article is normative legal research, which, in its development, is also known as doctrinal legal research, employing a case approach and a conceptual approach method. Keywords: Digital Forensics; Legality; Electronic Evidence